Pengembangan Kurikulum Pembelajaran Bahasa Arab Kontekstual Pada Madrasah Aliyah Raudhatul Muttaqien - Muhammad Tareh Aziz; Laili Mas Ulliyah Hasan; Riyadi Riyadi (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2024)
This research aims to analyze the development of a contextual Arabic language curriculum at Madrasah Aliyah Raudhatul Muttaqien, covering four main aspects: learning objectives, materials, methods, and evaluation. A contextual approach is essential for increasing the relevance of learning materials to students' daily lives, thus enhancing their interest and motivation in learning Arabic. This qualitative study employs a case study method, involving observation, interviews, and documentation for data collection. The findings indicate that the development of Arabic learning objectives at Madrasah Aliyah Raudhatul Muttaqien focuses on active and passive language skills, understanding Islamic literature, and integration with other subjects. The learning materials are based on the 2013 curriculum, supplemented with additional books for broader knowledge and practice. The predominant teaching method is the Sam'iyyah Syafahiyyah method to improve listening and speaking skills. Learning evaluation is conducted through formative and summative assessments integrated with technology to continuously monitor and enhance the learning process. The conclusion shows that the development of the contextual Arabic language curriculum at Madrasah Aliyah Raudhatul Muttaqien has been adjusted to meet the needs of students and the educational environment, using effective methods and evaluations to achieve the expected learning outcomes.